AB0107 Sonic hedgehog promotes survival and apoptosis resistance through smoothened protein in human umbilical vein endothelial cell. (23rd January 2014) - Zhu, S.; Huang, J.; Peng, W.; Wang, M.; Gu, J.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by chronic synovitis and pannus formation, leading to destruction of cartilage and bone. Sonic Hedgehog (Shh) signaling pathway plays significant role in regulating the morphogenesis during development and promotes angiogenesis in tumor. Earlier studies showed that endothelial cell apoptosis may play a major regulatory role in neovascularization. Objectives: We investigated the expression level of Smoothened(Smo) in endothelial cells in synovial tissue from patients with RA and analyzed the expression of Shh signaling pathway components(Shh, Ptch1, Smo and Gli1) in human umbilical vein endothelial cell line (EA.hy926 cell) and examined the effect of Smo protein on endothelial cell survival and apoptosis. Methods: The expression of Shh signaling pathway component Smo in synovial tissues from 4 RA patients and 4 patients with traumatic or meniscal injury was examined by immunohistochemistry assay. EA.hy926 cells were used as the model of human umbilical vein endothelial cells. Shh, Ptch1, Smo, Gli1 mRNA expression levels in EA.hy926 cells exposed to TNFα with or without specific Shh signaling pathway inhibitor(Cyclopamine) were detected by Real time-PCR, and the protein expression levels were measured by Western blot analysis.EA.hy926 cells were treated with different concentrations of Cyclopamine or transfected with the small interfering RNA (siRNA) specifically targeting Smo gene before exposure to TNFα and actinomycinD (ActD). The cell survival rate was detected by CCK-8 assay and the cell apoptotic rate was examined by flow cytometry. Results: Smo was highly expressed in synovial tissue in RA, especially in endothelial cells than that in control group. TNFα significantly increased the mRNA and protein expression of Shh signaling pathway components in EA.hy926 cells, while the expression was decreased in the presence of TNFα and Cyclopamine. EA.hy926 cells treated with Cyclopamine or transfected with Smo-siRNA showed a significant decrease in cell viability, with decreased cell survival rates and increased apoptotic rates, compared with those of the control group. Conclusions: Shh signaling pathway may play a role in the regulatory of apoptosis in endothelial cells in RA synovium and promote angiogenesis. References: Gravallese EM. Bone destruction in arthritis. Ann Rheum Dis. 2002. 61 Suppl 2: ii84-6. Dimmeler S, Zeiher AM. Endothelial cell apoptosis in angiogenesis and vessel regression. Circ Res. 2000. 87(6): 434-9. Varjosalo M, Taipale J. Hedgehog: functions and mechanisms. Genes Dev. 2008. 22(18): 2454-72. Disclosure of Interest: None Declared